International human rights law and practice - Bantekas, Ilias; Oette, Lutz (Cambridge : Cambridge University Press, 2016)
Human rights law is a complex but compelling subject that fascinates, but often confuses, students. International Human Rights Law and Practice explores the subject from a theoretical and practical perspective, guiding students to a rich understanding of the law. The second edition has been fully revised and updated, including two new chapters on children's rights and international criminal law, and new sections on a variety of topics, including the right to equality, the protection of refugees and the effect of foreign investment and sovereign debt on the enjoyment of human rights. In addition, new case studies and interviews with practitioners, NGO activists and policymakers show how theory is applied in real life. Student learning is supported by questions to stimulate seminar discussion and further reading sections that encourage independent study. The authors' clear and engaging writing style ensures that this new edition will continue to be required reading for all students of human rights law.
International human rights law and notions of human rights : foundations, achievements and challenges -- International human rights law : the normative framework -- Human rights in practice -- The United Nations Charter system -- The UN rights treaty system -- Regional human rights treaty systems -- Individual complaints procedures -- Civil and political rights -- Economic, social and cultural rights -- Group rights : self-determination, minorities and indigenous peoples -- The human rights of women -- Children's rights -- The right to development, poverty and related rights -- Victims' rights and reparation -- The application of human rights in armed conflict --Human rights and international criminal justice law -- Human rights and counter-terrorism -- Human rights obligations of non-state actors -- Globalisation and its impact on human rights.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Human rights; International law and human rights